TAMAN BACAAN KAMBOJA BANJARMASIN - Tiara Nurdini; Indah Mutia (ULM Press, 2024)
International surveys indicate that the literacy rate of Indonesians is among the lowest compared to other countries. This is because there are not enough reading facilities and because of the developments in electronic technologies, which provide instantaneous convenience. By offering non-formal reading facilities that are both fun and informative, a literacy park is one way to increase reading awareness among the general public. The city of Banjarmasin itself already has several libraries, one of which is in Taman Kamboja. However, the existing library in Kamboja Park has some circumstances or problems, and also rarely visited by the public. This is due to the hidden or secluded location of the library within the park, as well as the single function or limited facilities the library has offered. So the design problem is formulated as follows: How is the design of the Banjarmasin Kamboja Literacy Park, which can be a recreational space to introduce reading activities to the people of Banjarmasin City? The aim of designing the Cambodian Reading Gardens is to create an educational and recreational concept for a reading facility. The concept of Fun Reading is used to solve problems using the Flexibility Architecture Method which is deemed appropriate for realizing the design concept.